Circulating Glutamine and Alzheimer’s Disease: A Mendelian Randomization Study - Adams CD (Dove Medical Press, 2020)
Charleen D Adams Beckman Research Institute, Duarte, CA, USACorrespondence: Charleen D AdamsBeckman Research Institute, City of Hope,1500 E. Duarte Road, Duarte, CA, USATel +1 626-841-3931Fax +1 626-841-9204Email chaadams@coh.orgBackground: Alzheimer’s disease is a devastating neurodegenerative disorder. Its worldwide prevalence is over 24 million and is expected to double by 2040. Finding ways to prevent its cognitive decline is urgent.Methods: A two-sample Mendelian randomization study was performed instrumenting glutamine, which is abundant in blood, capable of crossing the blood-brain barrier, and involved in a metabolic cycle with glutamate in the brain.Results: The results reveal a protective effect of circulating glutamine against Alzheimer’s disease (inverse-variance weighted method, odds ratio per 1-standard deviation increase in circulating glutamine = 0.83; 95% CI 0.71, 0.97; P = 0.02).Conclusion: These findings lend credence to the emerging story supporting the modifiability of glutamine/glutamate metabolism for the prevention of cognitive decline. More circulating glutamine might mean that more substrate is available during times of stress, acting as a neuroprotectant. Modifications to exogenous glutamine may be worth exploring in future efforts to prevent and/or treat Alzheimer’s disease.Keywords: Alzheimer’s disease, dementia, metabolism, glutamine, Mendelian randomization, prevention